International Investor Sentiment and Emerging Equity Markets in Central and Eastern Europe - Sokalska, Magdalena (Journal of Reviews on Global Economics, 2015)
This paper uses the vector Markov switching method of Hamilton (1990) to measure market sentiment in a group of countries. We investigate the apparent co-movement of equity returns in the Czech Republic, Hungary and Poland. We argue that the main underlying forces moving stock returns in small open emerging markets are of an exogenous nature. The main factor driving prices in the region is modeled as an unobservable variable labeled "international investor sentiment". This latent variable is represented as a two-state Markov chain and makes stock returns switch from a growth regime to a depression regime, or in the opposite direction. In such a framework, the stock return process comes from a mixture of two multivariate normal distributions. The estimated latent variable shows significant correlation with a number of data series on global capital flows, mutual fund flows, regional emerging and developed markets’ equity returns as well as with other popular market sentiment or economic uncertainty indicators. It does not show a strong association with a comprehensive set of contemporaneous local economic factors with the exception of the quarterly change in industrial production.